Effectiveness of passive design features and active installations for security in large shopping centres in Abuja, Nigeria - Folaranmi, Adedayo Olatunde; Eunice, Bamidele Oluwatosin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Nigerians have been witnessing a class struggle among developers and investors competing for who builds the largest shopping centres. However, some of these shopping centres are being abused by a few patronisers who hide under the guise of shopping to engage in some indecent and criminal activities. The shopping centre business concept has not only boosted the country’s gross domestic product (GDP) and created jobs but has provided recreation and relaxation centres for those who have the financial capacity to patronize them. A major challenge is that the building design and security planning phases of most of these shopping centres seem to be running independently of each other, as opposed to working together to achieve a fully secured building. This paper examines the effects of passive design features on active security installation in large shopping centres. To achieve the desired objectives, data obtained through primary and secondary sources comprised the use of structured observation schedules and questionnaires. A total of 240 questionnaires were distributed to security personnel in 30 selected shopping centres using a stratified sampling method. Descriptive statistics was used to analyse the data obtained. The results showed the level of effectiveness of the existing passive design features in the installation of security elements. It is recommended that the design of shopping centres bearing cognizance of passive design should extend to the provision of maximum security